The “big five” phytochemicals targeting cancer stem cells: curcumin, EGCG, sulforaphane, resveratrol and genistein - Naujokat, Cord; McKee, Dwight L. (Current medicinal chemistry, 2021)
Cancer stem cells (CSCs) constitute a subpopulation of tumor cells that possess - self-renewal and tumor initiation capacity, and the ability to give rise to...